Influence of smoking habits and place of residence on the risk of lung cancer among workers in one rock-wool producing plant in Denmark. - Olsen, Jørgen H.; Jensen, Ole M.; Kampstrup, O. (Scandinavian Journal of Work, Environment & Health, 1986)
Cancer incidence was studied among 5,317 employees in one rock-wool production plant in Denmark. During the period 1943--1982 a marginally significant excess of 240 cancer cases was observed versus 211.0 cases expected. Among the subgroup of male workers an increasing risk with time since first employment was observed for cancer of the buccal cavity and pharynx, cancer of the respiratory system, and cancer of the bladder, of which only the excess of the first-mentioned reached significance. The increased risk of lung cancer among male workers with 20 or more years since first employment, which was not significantly in excess of 1.0, although still compatible with a two- to threefold increase according to conventional 95% confidence limits, could not be explained by deviations in local lung cancer incidence, place of residence among the rock-wool male workers, or smoking habits prevailing among unskilled workers in the eastern part of Denmark. The number of cases, however, was too small to exclude the effect of chance in this single investigation.